1993
DOI: 10.1093/eurheartj/14.9.1163
|View full text |Cite
|
Sign up to set email alerts
|

Radionuclide assessment of regional differences in left ventricular wall motion and myocardial perfusion in idiopathic dilated cardiomyopathy

Abstract: Regional variations in left ventricular contractility and myocardial perfusion are frequent in idiopathic dilated cardiomyopathy and might result from an increase in left ventricular wall stress responsible for regional wall motion abnormalities. The aim of the study was to perform radionuclide studies in patients with idiopathic dilated cardiomyopathy to assess regional left ventricular wall motion and myocardial perfusion abnormalities in this myocardial disease. We studied 29 men referred with idiopathic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 0 publications
1
30
0
Order By: Relevance
“…Besides focal myocardial fibrosis, 22,[27][28][29] recent studies have suggested that perfusion and metabolism may be affected by endothelial dysfunction in DCM. [30][31][32] LBBB is known to impair LV mechanical function and is an important predictor of cardiac mortality in patients with HF caused by DCM. 10,33 Previous studies found that perfusion and glucose metabolism were reduced in cases with LBBB, [34][35][36][37][38][39][40][41][42] and the extent of scarring correlates with QRS duration.…”
Section: Discussionmentioning
confidence: 99%
“…Besides focal myocardial fibrosis, 22,[27][28][29] recent studies have suggested that perfusion and metabolism may be affected by endothelial dysfunction in DCM. [30][31][32] LBBB is known to impair LV mechanical function and is an important predictor of cardiac mortality in patients with HF caused by DCM. 10,33 Previous studies found that perfusion and glucose metabolism were reduced in cases with LBBB, [34][35][36][37][38][39][40][41][42] and the extent of scarring correlates with QRS duration.…”
Section: Discussionmentioning
confidence: 99%
“…14,15,17,18,27 We also limited our analysis to DCM patients with widened QRS complexes, and it remains possible that some individuals with more narrow complexes might also benefit. Previous studies have reported regional wall motion abnormalities, heterogeneous wall stress, and myocardial perfusion in DCM patients with normal-appearing epicardial vessels, 28,29 although none reported QRS durations to test correlations with these phenomena. Certainly, surface ECG-based estimates may underestimate the temporal spread of depolarization if early and late portions have relatively low voltages.…”
Section: Study Design Limitationsmentioning
confidence: 99%
“…IDC patients have a marked heterogeneity of regional ventricular function [59,60]; this mirrors the heterogeneity of regional wall stress (increased stress, decreased function), which is one of the main determinants of MVO 2 [61,62]. 11 C-acetate imaging [63,64] demonstrated regional heterogeneity of myocardial oxidative metabolism (most commonly increased in the lateral wall), where regional oxidative metabolism was related to regional function.…”
Section: Metabolically Trapped Fatty Acids and Acetatementioning
confidence: 99%